The reasoning behind the envisioned educational trajectories of young people from Finnish and immigrant origins. Issue 4 (1st October 2020) - Varjo, Janne; Kalalahti, Mira; Jahnukainen, Markku
ABSTRACT: Transitions from one level of education system to another and from education to work are structured by socio-economic and institutional structure factors, while at the same time they are appropriated by individuals in their biographical constructions. Patterns to career trajectories are also dependent on social class, immigrant origin and level of academic achievement. This paper elaborates the ways young people are envisioning their post-comprehensive trajectories in Finland. Based on an analysis of qualitative interview data (n = 113) with immigrant- and Finnish-origin youths in the final year of their comprehensive education (ninth grade), patterns of envisioned educational trajectories are identified and the reasoning behind them recognised. The analysis introduces six possible envisioned educational trajectories, based on combinations of envisioned educational choices and occupational destinations. They portray the multiple relational aspects and intertwining processes of the decision-making processes, but also underline the nature of them as self-made reasonings of skills, stress, friends, life management and aspirations. Study guidance and counselling should support the decision-making processes as a part of the holistic life-design process.